2004
DOI: 10.1128/jcm.42.1.79-82.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Respiratory Virus Culture When Screening with R-Mix Fresh Cells

Abstract: Use of R-Mix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 13 publications
2
39
1
3
Order By: Relevance
“…However cryopreserved R-Mix ReadyCells did detect 55% more adenovirus after 1 day than conventional culture. Dunn et al reported a similar detection rate (68.6%) at 1 day and mentioned the requirement of extended incubation (Dunn et al, 2004). In our extended incubation the detection rate increased to 90% after 3 days.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However cryopreserved R-Mix ReadyCells did detect 55% more adenovirus after 1 day than conventional culture. Dunn et al reported a similar detection rate (68.6%) at 1 day and mentioned the requirement of extended incubation (Dunn et al, 2004). In our extended incubation the detection rate increased to 90% after 3 days.…”
Section: Discussionsupporting
confidence: 82%
“…1016/j.jcv.2008.03.015 Conventional viral culture, which has been the gold standard for respiratory virus diagnosis, may often require several days to detect respiratory viruses, as well as several specific cell lines for each respiratory virus. Recently R-Mix, a combination of human lung carcinoma cells and mink lung cells (strains A-549 and Mv1Lu, respectively) co-cultivated in a balanced single monolayer was reported to exhibit sensitivity for respiratory virus detection comparable with other viral detection methods (Barenfanger et al, 2001;Dunn et al, 2004;Fong et al, 2000;Huang et al, 2002;St George et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Importantly, a small number of studies have described the immediate culture of pediatric patient specimens as having a very high sensitivity for RSV and influenza virus detection when cell culture was performed on site (20,37). In addition to the importance of immediate virus isolation for accurate cell culture results, the methodology is also heterogeneous and the sensitivity for the detection of these viruses differs when different cell culture methods are used (12,27,29,42).…”
Section: Culture Pcrmentioning
confidence: 99%
“…Isolation of RSV and influenza virus with R-mix cells can provide positive culture results in as little as 1 to 2 days, whereas conventional tube culture methods typically provide a 5-to 6-day turnaround time for positive specimens (12,42). The average turnaround times in this study for specimens positive by tube cell culture for RSV and influenza virus were 10.6 and 8.8 days, respectively.…”
Section: Culture Pcrmentioning
confidence: 99%
“…Viral culture is still considered the "gold standard" method, but traditional culture generally requires at least 3 days or longer to obtain a positive result. Rapid viral culture methods using "shell vial" assays have been applied to speed up the time to detection (8)(9)(10)(11). Nucleic acid amplification methods offer very high test sensitivities and same-day results, but there are no FDA-cleared nucleic acid amplification tests for influenza virus detection.…”
mentioning
confidence: 99%